La devolución etnográfica cómo dispositivo metodológico: la producción simultánea de un documental etnográfico y un video promocional en etnoempresas turísticas en la selva central peruana - Álvarez Castillo, Luz María (2022)
The aim of this paper is to recognize and analyze the materiality, agendas and routes of the audiovisuals resulting from practice as research: the whole process of production of an audiovisual as a methodology for academic research. Likewise, the present work opens the dialog for an exchange (Mauss, 2002) with our collaborators as an intervention device (cita aqui). The empirical reference is based on my ethnographic approach to ethno-tourism projects managed by a group of indigenous entrepreneurs in the Central Peruvian Jungle, who while promoting ethno-tourism in the region, explore and question their own indigeneity. The central methodology of this research is to simultaneously produce an ethnographic audiovisual and a promotional video as an exachange. We found that the camera, as well as the audiovisuals, are things that become an extension of the body and experiences of the anthropologist-filmmaker, researcher / producer, becoming agents that define and constrain the field of research.